3.6 LONGITUDINAL CHANGES IN AORTIC RESERVOIR FUNCTION INDEPENDENTLY PREDICT DECLINING RENAL FUNCTION AMONG HEALTHY INDIVIDUALS - Rachel Climie; Dean Picone; James Sharman (Artery Research, 2016)
Objectives: Aortic reservoir function independently predicts end organ damage in cross sectional analyses. However, longitudinal associations are more important regarding causation, but this has never been examined and was the goal of this study. Methods: Aortic reservoir function (excess pressure integral [xsP] and aortic reservoir pressure), aortic stiffness, brachial and central blood pressure (BP), and renal function (estimated glomerular filtration rate [eGFR]) were recorded among 33 healthy individuals (57±9 years 55% male) at baseline and after an average 3.0±0.3 years. Results: Over the follow up period there was no significant change in brachial BP (p>0.05), whereas there was a trend for xsP (p=0.061) and central BP (p=0.068) to increase. On the other hand, aortic stiffness and blood glucose increased significantly (p<0.05 both). The change over time in xsP (but not aortic stiffness) was significantly related to the change in eGFR (r=−0.370, p=0.044) and this remained independent age, 24 hour systolic BP and body mass index (β=−0.031, p=0.045), but not blood glucose (β=−0.031, p=0.053). There was no interaction between the change in glucose and change in xsP. Conclusions: Aortic reservoir function, as determined by excess pressure, is independently associated with a decline in renal function among healthy people followed over 3 years. These novel findings indicate the need to determine the underlying physiological determinants of aortic reservoir function.